Lactoferrin attenuated urban particulate matter-induced nephrotoxicity by regulating the CSF2/CENPE axis. (1st February 2023) - Liu, Wen-Chih; Chiu, Hui-Wen; Chou, Chu-Lin; Chiu, Yu-Jhe; Lee, Yu-Hsuan
Abstract: Several epidemiological studies regarding the adverse effect of air pollution have notably accelerated in recent years. Urban particulate matter (PM) gains access to the respiratory system and translocates into the circulation to affect several tissues, such as the liver and kidneys. Lactoferrin is a substance belonging to the non-heme iron-binding glycoprotein which is present in breast milk and other exocrine fluids. Lactoferrin is protective against many pathophysiological conditions. In the present study, we explored the potential influence of lactoferrin on PM-induced nephrotoxicity. We found that lactoferrin rescued PM-induced cell death but did not affect apoptosis in human kidney cells. Lactoferrin decreased necroptosis and fibrosis but increased autophagy in human kidney cells. Furthermore, the gene expression profiles of PM and lactoferrin were analyzed by RNA sequencing. The transcriptional profiles were uploaded and analyzed by ingenuity pathway analysis software and gene set enrichment analysis. The results showed that the crucial role of the CSF2/CENPE pathway was involved in human kidney cells treated with PM and lactoferrin. In a mouse model, lactoferrin ameliorates PM-induced nephrotoxicity by regulating necroptosis, fibrosis, autophagy and the CSF2/CENPE axis. In summary, these findings showed that lactoferrin could be a novel therapeutic or preventive agent for renal disorders caused by airborne PM pollution. Graphical abstract: Image 1 Highlights: PM-induced nephrotoxicity through necroptosis results in fibrosis. Lactoferrin prevents PM-induced cell death from necroptosis. Lactoferrin restrains PM-induced fibrosis but increases autophagy in HK-2 cells. CSF2/CENPE pathway is involved in lactoferrin ameliorated PM-induced nephrotoxicity.